2017
DOI: 10.3117/plantroot.11.40
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of root elongation by pyridinecarboxylic acids known as novel cut flower care agents

Abstract: Pyridinedicarboxylic acid (PDCA) analogs, including 2,3-, 2,4-, 2,5-, 2,6-, 3,4-and 3,5-PDCA, accelerate flower opening and retard senescence of spray-type carnation flowers. In addition the present study revealed that 2,3-PDCA promoted root elongation in lettuce, carrot and rice seedlings, whereas 2,4-PDCA inhibited it. Then, the action of PDCA and pyridinecarboxylic acid (PCA) analogs on root elongation was further examined using rice seedlings. 2,3-, 3,4-and 3,5-PDCA promoted rice root elongation, whereas 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 11 publications
3
10
0
Order By: Relevance
“…These finding suggested that the carboxyl group at position 3 of the pyridine ring is needed for the promotion of flower opening. This agreed with a previous experiment in which 3-carboxylic acid was necessary to promote root elongation in rice seedlings (Satoh and Nomura, 2017). However, in the present study, both 3-PCA and 3-PCA amide were equally effective in promoting flower opening.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…These finding suggested that the carboxyl group at position 3 of the pyridine ring is needed for the promotion of flower opening. This agreed with a previous experiment in which 3-carboxylic acid was necessary to promote root elongation in rice seedlings (Satoh and Nomura, 2017). However, in the present study, both 3-PCA and 3-PCA amide were equally effective in promoting flower opening.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, 3-PCA, and probably 3-PCA amide, promoted only flower opening, but did not inhibit ethylene production, resulting in a shorter vase life than that of 2,4-PDCA-treated flowers. Overall, the present findings revealed that some PCA analogs, represented by 3-PCA, promoted flower opening in spray-type 'LPB' carnations, similar to the previously shown promotion of root elongation in rice seedlings (Satoh and Nomura, 2017).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Unexpectedly, however, we found that both agents could stimulate adventitious root formation in rootcut seedlings and stems of some vegetables. In the present study, we characterized the action of NSC-Base ® , using several plant species and active ingredients of NSC-Base ® , and their interaction with a root elongation stimulator, 3-pyridinecarboxylic acid (Satoh and Nomura 2017).…”
Section: Qualitative Analysis For Promotion Of Adventitious Root Formmentioning
confidence: 99%